MANTRA NELAYAN BAJO DI SUMBAWA: TINJAUAN BENTUK DAN ISI (MAKNA) - . Syarifuddin (Humaniora, 2008)
Fishermen in Bajo always use magic formulae to communicate with the highest creatures and their nature. The belief of the Bajo people on the magic formulae can be seen in many collective life aspects. Magic formulas are formed by linguistics costruction (main sentences) revealing the Bajo’s culture itself. The magic formula of the Bajo fishermen were formed by using certain and specific linguistic construction expressing the notions of request and statements. Quite a number of the magic formulae were constructed using inversions. By using the magic formulae, the fishermen of Bajo create relationship with the creature of the highest power and the environment. This relationship is expected to support them in gaining what they have requested.